2018
DOI: 10.1111/apa.14387
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence and low spontaneous eradication rate of Helicobacter pylori infection among schoolchildren aged 7–12 years

Abstract: The prevalence of the H. pylori infection among Chinese schoolchildren aged 7-12 was high and spontaneous eradication was low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 16 publications
(24 reference statements)
1
18
1
1
Order By: Relevance
“… 1 The incidence of Hp infection in children in China is high; and its natural remission rate is low. 2 In recent years, the eradication rate of Hp infection has decreased. The eradication rate of Hp infection treated by triple therapy has been reported to be lower than 80%.…”
Section: Introductionmentioning
confidence: 99%
“… 1 The incidence of Hp infection in children in China is high; and its natural remission rate is low. 2 In recent years, the eradication rate of Hp infection has decreased. The eradication rate of Hp infection treated by triple therapy has been reported to be lower than 80%.…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al reported a statistically significant decrease in the H pylori infection rate in symptomatic children between 2005 (25.6%) and 2017 (12.8%) in China. However, infection rates remain higher in some groups of children, dependent on factors such as low socioeconomic status and bad sanitary conditions as was concluded in studies from Poland, Peru, China, and Ethiopia …”
Section: Epidemiologymentioning
confidence: 90%
“…The epidemiology of H pylori is rapidly changing, as shown by the high number of epidemiologic studies published in the last year. The world prevalence of H pylori varies significantly, from 2.5% in Japan to 34.6% in Ethiopia (Table ). Nonetheless, a decreasing trend in the prevalence of H pylori infection among children is being observed.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent epidemiologic studies have reported a decreasing prevalence of pediatric H. pylori infection pointing out a significant difference between 25.6% in 2005 and 12.8% in 2017 [ 14 ]. Nevertheless, wide variations were reported among different populations in terms of prevalence mostly depending on the socio-economic status [ 7 , 8 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: New Insights On Pediatric H Pylori Infectionmentioning
confidence: 99%